HUKUM ISLAM FUNGSIONAL DI TENGAH PERUBAHAN SOSIAL - Ahmatnijar, Ahmatnijar (IAIN Padangsidimpuan, 2019)
If social change is relentless and can be engineered but cannot escape from the legal aspect, then the thought of developing Islamic law must also be engineered and must not be stopped so that it remains within the functional sphere